단일 환자에서 디지털 및 전통적인 워크플로우로 제작한 두 쌍의 총의치를 장착하여 비교평가한 증례 보고 - 김상현; 오경철; 박지만; 김지환; 문홍석; Kim, Sang Hyun; Oh, Kyung Chul; Park, Ji Man; Kim, Jee Hwan; Moon, Hong Seok (Taehan Chikwa Poch'ol Hakhoe chi, 2021)
Application of digital technology in dental treatments can simplify the treatment process and reduce patient discomfort. In regards of digital complete dentures, several commercial systems are available. However, these systems are not being routinely applied in Korea. In this case report, comparative analyses were performed regarding the two sets of complete dentures fabricated in digital and conventional workflow in a single patient. Complete dentures made with digital workflow were able to form an ideal occlusion because customized teeth were used. Compared to that, there were also limitations such as lower retention of mandibular dentures, so we would like to report this. 치과치료에 디지털 기술을 접목함으로써 치료 과정을 단순화하고 환자의 불편감을 줄여줄 수 있다. 디지털 기술을 활용한 총의치의 경우 여러 상업적인 시스템들이 나와 있으나 아직 국내에서는 보편적으로 사용되고 있지 않다. 본 증례 보고에서는 단일 환자에서 디지털 및 전통적인 치료 술식으로 제작한 두 쌍의 총의치를 장착한 뒤 이에 대한 환자의 만족도와 유지력, 안정성, 적합도를 비교하였다. 디지털 치료 술식으로 제작한 총의치는 개인화되어 디자인된 밀링된 치아를 이용했기 때문에 이상적 교합을 형성할 수 있었으며, 디지털 치은 디자인을 통해 심미성 또한 확보하여 적절한 기능적, 심미적 임상결과를 보였으나, 전통적 제작 방식에 비해 하악 의치의 유지력이 떨어지는 등의 한계 또한 존재하였기에, 이에 대하여 보고하고자 한다.